Dinamika Kerukunan Antar Umat Beragama di Kota Singkawang Sebagai Kota Toleransi: The Dynamics of Interfaith Harmony in Singkawang City as a City of Tolerance - Widiatmaka, Pipit; Saputra, Randi; Irfan, Muhammad; Hendri Nuryadi, Muhammad; Putri Ramadhani, Fadhilah (Jurnal Bimas Islam, 2025)
West Kalimantan, especially Sambas Regency, which has expanded into three regions (Sambas, Bengkayang, and Singkawang), has a bad history related to conflicts between religious communities. This occurs because of a lack of tolerance for differences. This research aims to find out the harmony of life between religious communities in Singkawang City and to find out the impact of the lives of people in Singkawang City on diversity in Indonesia. This research approach uses a qualitative approach with a descriptive research method. This research is conducted in the Singkawang City. The data collection in this study uses interviews, observations, and documentation, while the data analysis uses interactive. The harmony between religious communities in Singkawang City is well-established, thanks to the city's regulations that promote tolerance in people's lives. As a result, Singkawang has consistently been ranked first in Indonesia for its tolerance. The impact of interfaith harmony in Singkawang City on diversity in Indonesia is very significant because interfaith harmony in Singkawang City can be a model for all regions in Indonesia.